A Meta Analysis of the Relationship between Organizational Justice and Job Satisfaction: The Case of Turkey - Hakan Yalçın; Yeliz Yalçın (Istanbul Business Research)
The aim of this study is to examine the relationship between organizational justice and job satisfaction using metaanalysis. In this context, the Gazi University Library data base was used to identify the research which was to be included in the analysis. In the first stage, the research items which were published in the period 2010.01-2017.10 and which included samples inside the borders of Turkey were reviewed. In the second stage, studies based on appropriate criteria were identified among a total of 53 studies. The results obtained using the correlations of 19 appropriate studies showed that the correlation between organizational justice and job satisfaction was 0.605. The sub-dimensions of both variables were positively correlated and statistically significant. It was concluded that the distributional justice from organizational justice dimension was the most important dimension in job satisfaction.